INOVASI DAKWAH PENDIDIKAN REMAJA BERBASIS MASJID: STUDI KASUS PROGRAM PESANTREN SUBUH - Kharisma Putra Budi Prasojo; Isa Saleh; Ahmad Faiz Khudlari Thoha; Diki Taufikkurrohman (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This study aims to explore the innovation of the Pesantren Subuh program as an inclusive mosque-based religious education model for adolescents. Using a qualitative method and case study approach, this research examines the implementation of the Pesantren Subuh program at Al Muhajirin Karangpilang Mosque in depth. Data were collected through in-depth interviews with program caregivers, students, and parents, as well as field observations. The findings indicate that the program effectively addresses the gap in religious education for urban adolescents by utilizing a flexible early morning schedule that does not interfere with school activities. The program also involves parents as key supporters in fostering religious habits in children. The data analysis using the Gioia method suggests that the key success factor is the involvement of parents in encouraging and motivating their children’s participation. With this model, the Pesantren Subuh program not only successfully fosters religious character in adolescents but also has the potential to be adopted as a mosque-based religious education model in other regions.